2017
DOI: 10.2147/cia.s117597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese herbal formula Erxian decoction for treating osteoporosis: a systematic review

Abstract: PurposeThe aim is to systematically assess the effectiveness and safety of Chinese herbal formula Erxian decoction (EXD) for treating osteoporosis.Materials and methodsSix databases were searched from inception through September 17, 2016, without language restriction. All randomized controlled trials of EXD for osteoporosis were included. One or more outcome measures including fracture, change in bone mineral density (BMD), pain symptom improvement, bone biochemical markers, quality of life, adverse event or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…Accordingly, there is a clear requirement for newer therapeutic options or agents. In recent years, the increasing use of complementary and alternative medicine, including Chinese herbal medicine, for treating osteoporosis has attracted widespread attention (Li et al, 2017; Wang et al, 2018; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there is a clear requirement for newer therapeutic options or agents. In recent years, the increasing use of complementary and alternative medicine, including Chinese herbal medicine, for treating osteoporosis has attracted widespread attention (Li et al, 2017; Wang et al, 2018; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional herbal medicines have been used as complementary and alternative treatment options for osteoporosis patients for a long time. Some reviews have assessed the efficacy and safety of different Chinese multiherb prescriptions in treating osteoporosis, such as Liuwei Dihuang decoction and Erxian decoction [ 19 , 20 ]. But considering the diversity of Chinese herbal medicine, we have reason to believe that there is still huge part of diverse herbs compound recipes which remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression profiles showed that the common genes that were upregulated during EXD extract treatment were related to the MAPK signaling pathway, indicating that EXD exerted its effect by regulating the MAPK signaling pathway. A clinical trial showed that EXD improved bone mineral density at both the lumbar spine and the femoral head in postmenopausal women, demonstrating an osteoprotective effect[95]. However, no study has demonstrated its effect on the incidence rate of fracture.…”
Section: Small Molecules Regulate Mscs Osteogenic Cell Fatementioning
confidence: 99%